FORMULASI DAN EFEKTIVITAS SEDIAAN GEL PEWARNA RAMBUT ALAMI EKSTRAK BUAH MERAH (Pandanus conoideus L.) - Muhammad Andy Irfan; Irwandi Irwandi; A.M. Muslihin (Universitas Pendidikan Muhammadiyah Sorong, 2025)
Synthetic dyes are a type of dye that contains chemical substances as their main component, and to date, they remain a primary choice in hair coloring processes due to their excellent color results and long-lasting durability. However, the discovery of several cases of contact dermatitis resulting from the use of synthetic hair dyes has highlighted the potential side effects of these dyes. One common effect is irritation to the scalp and hair. Red fruit (Pandanus conoideus L.) is a Papua-specific plant rich in carotenoids. To facilitate its use, red fruit can be formulated into a hair dye gel preparation. Gel is chosen for its practicality, ease of absorption, formation of a film layer that is easy to clean, and provision of a cooling effect on the skin. The stages of this research include sample preparation, formulation of hair dye gel at concentrations of 6%, 8%, and 10%, physical characteristic testing, and effectiveness testing of the red fruit ethanol extract hair dye gel preparation. The results showed that 141.9 grams of thick extract were obtained from 750 grams of dry simplicia, resulting in a yield of 70.45%. The physical characteristic and effectiveness testing of the hair dye gel preparation at concentrations of 6%, 8%, and 10% were satisfactory. The ethanol extract of red fruit can be formulated into a hair dye gel preparation at concentrations of 6%, 8%, and 10%, with comparable coloring results.